Trauma as Pathogenesis of a Plantar Forefoot Fibrolipoma: First Case and Review of the Literature - Juliana S. P. Vasconcelos; Faris Gharaibeh; Hans-Christoph Nittinger (Case Reports in Surgery)
Lipomas and their variants are benign soft-tissue tumors that occur at any age and most frequently on the upper back and neck, shoulder, and abdomen. The foot is a relatively uncommon site for soft-tissue neoplasia and the etiology is not usually related to trauma. We describe a case of a pedunculated fibrolipoma of the forefoot that originated from a cut wound at the Atlantic Ocean. A brief review of the literature is also given.